Efeitos da terapia laser de baixa intensidade na regeneração do nervo isquiático após neurorrafia término-terminal em ratos - Bernardo, Gabriele Candido (2018)
Peripheral nerve injuries occur through numerous traumatic, metabolic, inflammatory, infectious processes, including car accidents, work, fractures, dislocations, firearms projectiles, falls, blunt or penetrating trauma, resulting in partial or total loss of motor function, sensorial and autonomic in the involved segments, leading to functional disabilities, which in turn generate damage to the state system, in cases of early retirement. After an injury, recovery may eventually occur, but through a slow and often incomplete process. Thus, several attempts have been made to improve and / or accelerate the regeneration of peripheral nerves. Among physical resources, Low Intensity Laser Therapy (TLBI) is perhaps the least known in terms of its effects on biological tissues and the application parameters in nerve lesions. To date, no specific therapeutic window has been established for optimal dosimetry of treatment, so prior to the use of this new therapy as a therapeutic modality, there is a need to investigate the dose-response effects of such treatment in in vivo studies in order to determine effectiveness and safety. Thus, this study aims to analyze the effects of TLBI, with energies of 2 J, 4 J and 6 J, on the regeneration of the sciatic nerve of rats after completion of the terminal-terminal neurorrhaphy. For this, 72 male Wistar rats were distributed in 6 groups with 12 animals each: Control Group (GC), Control Group (GCD), Sham Group (GS), Laser Group 2J (GL2), Group Laser 4J (GL4) and Laser Group 6J (GL6), with the last three receiving TLBI for 45 days, 3x / week. In all analyzes, GC presented the best result, with no significant difference between groups GL2, GL4 and GL6. It was concluded that TLBI promoted a functional and morphometric improvement after completion of the term-terminal neurorrhaphy of the sciatic nerve in rats.